Agile 2007 (Agile 2007) 2007
DOI: 10.1109/agile.2007.22
|View full text |Cite
|
Sign up to set email alerts
|

Does the XP environment meet the motivational needs of the software developer? An empirical study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…Beecham et al [28], based on the general research claim that agile methods lead to higher motivation, carried out a case study with five mature XP teams and concluded that agile practices are somewhat supportive to the motivation of software engineers regarding peer relationships. However, the XP environment did not support individual needs of recognition, clear career progression, and variety of work.…”
Section: Related Case Studiesmentioning
confidence: 98%
“…Beecham et al [28], based on the general research claim that agile methods lead to higher motivation, carried out a case study with five mature XP teams and concluded that agile practices are somewhat supportive to the motivation of software engineers regarding peer relationships. However, the XP environment did not support individual needs of recognition, clear career progression, and variety of work.…”
Section: Related Case Studiesmentioning
confidence: 98%
“…To be successful, a flexible process should consider these factors and provide adequate support for knowledge sharing. As identified in [2], agile practices (XP), seems to support developers motivational needs (RQ1). Their motivational needs included, among others: knowledge sharing, support for the less experienced and knowledge acquisition.…”
Section: Human Factors -Skills Experiences and Attitudesmentioning
confidence: 92%
“…technical success, challenging technical problems (Tanner, 2003;Ramachandran and Rao, 2006) and peer interaction (Tanner 2003;Procaccino et al 2005). We found previously (Beecham et al, 2007) an increasing awareness of the importance of motivating software developers.…”
Section: Introductionmentioning
confidence: 89%